209k views
7 votes
Help plz ASAP !!!!!!!!!!!!!!!!!!!!!!!!!!

Help plz ASAP !!!!!!!!!!!!!!!!!!!!!!!!!!-example-1
User Og
by
4.7k points

2 Answers

11 votes

Answer:-2

Explanation:

User Drew
by
5.3k points
9 votes

Answer:

-2

Explanation:

Let's solve your equation step-by-step.

−(3v+1)+7(6v+6)=−37

Step 1: Simplify both sides of the equation.

−(3v+1)+7(6v+6)=−37

−3v+−1+(7)(6v)+(7)(6)=−37(Distribute)

−3v+−1+42v+42=−37

(−3v+42v)+(−1+42)=−37(Combine Like Terms)

39v+41=−37

39v+41=−37

Step 2: Subtract 41 from both sides.

39v+41−41=−37−41

39v=−78

Step 3: Divide both sides by 39.

39v

39

=

−78

39

v=−2

Answer:

v=−2

User Mwerschy
by
5.1k points